INVESTIGATE THE FACTORS THAT INFLUENCE FOREIGN TOURISTS' DECISION TO VISIT GARUDA WISNU KENCANA - Fuadi Afif; Rachmadi, Hari (Jurnal Pendidikan dan Perhotelan (JPP), 2023)
The goal of this study was to examine the variables that affect foreign tourists' decisions to visit the Garuda Wisnu Kencana Cultural Park. The purpose of this study is to answer the following research questions: "Do push and pull factors affect people's decisions to travel abroad? ", and "Of these two factors, which one has the most significant impact on people's decisions to travel abroad to Garuda Wisnu Kencana Cultural Park?" In order to conduct this study, push and pull factors for foreign visitors to the Garuda Wisnu Kencana Cultural Park were examined. The incidental sampling technique was used in this study, and a sample of 30 foreign visitors to the Garuda Wisnu Kencana Cultural Park served as the respondents. The analytical approach used is quantitative analysis, which includes the Coefficient of Determination Test, the Partial T Test, the F Test, the Multiple Linear Regression Analysis Test, and the Classical Assumption Test. The study's findings indicate that these two factors can have an impact on foreign tourists' decisions to visit either simultaneously or jointly. The Anova test or F test, which shows that Ha1 is accepted when the calculated F value > F table is 27.543 > 3.34, supports this. The results of the second study's regression tests, which are techniques for establishing the causal relationships between two variables, are as follows: Y = 2.195 + 1.086X1 + 0.708X2. The push factor (X1) and pull factor (X2) T test results are 4.686 and 5.048, respectively, with 0.000 and 0.000 as significant values. These results show that the X2 variable, also known as the Attractor Factor, has the highest tcount value, with a tcount>ttable (5.048>2.051) and a significant value of 0.0000.05. These findings suggest that the pull factor variable has a significant impact on visitors' decisions to travel to the Garuda Wisnu Kencana Cultural Park from abroad. Ha2 is therefore acknowledged. R2, also known as the coefficient of determination, has a value of 0.671, or 67.1%. The choice of foreign tourists to visit Garuda Wisnu Kencana Cultural Park is influenced by these two factors; the remaining 35.3% is influenced by factors outside the scope of the research model. Examples include a tour guide, transportation, accessibility, lodging, and so forth.